2005
DOI: 10.1093/neurosurgery/57.4.e815
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Hemangioma in the Superior Sagittal Sinus as a Rare Cause of Intracranial Hypertension in a Child: Case Report

Abstract: A tumor growing into a venous sinus is a rare cause of venous outflow impairment and may generate the clinical signs of idiopathic intracranial hypertension. This case emphasizes the importance of multiple complementary imaging modalities and the efficacy of a direct surgical approach, which allowed resolution of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…6 Intracranial hemangiomas are extremely rare; only 20 biopsy-proven cases were found in the literature. 1,2,5,8,10,11,13,17,18,[20][21][22][23][24] With the exception of 4 cases, 11,20,23 the reported primary mode of treatment was neurosurgical resection, of which complete resection was achieved in 12 of the 16 cases. In the other 4 cases, 13,17 only subtotal resection was possible, and additional surgery or radiotherapy was needed to achieve tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…6 Intracranial hemangiomas are extremely rare; only 20 biopsy-proven cases were found in the literature. 1,2,5,8,10,11,13,17,18,[20][21][22][23][24] With the exception of 4 cases, 11,20,23 the reported primary mode of treatment was neurosurgical resection, of which complete resection was achieved in 12 of the 16 cases. In the other 4 cases, 13,17 only subtotal resection was possible, and additional surgery or radiotherapy was needed to achieve tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…The literature emphasizes a prevalence of these tumors in childhood, with eight cases reported (1,2,5,9,10,16,17,19), whereas our experience refer to adult patients. …”
Section: Discussionmentioning
confidence: 72%
“…Intracranial capillary hemangiomas are rare, with only 14 histologically confirmed cases previously reported (1,2,5,9,10,(13)(14)(15)(16)(17)19). The literature emphasizes a prevalence of these tumors in childhood, with eight cases reported (1,2,5,9,10,16,17,19), whereas our experience refer to adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brotchi et al have described the case of a child presenting with elevated ICP secondary to an ICH that caused sagittal sinus obstruction. 3 Other authors have reported children presenting with signs and symptoms of elevated ICP secondary to the shear size of the ICH itself. 4,5,19 One infant died of a subarachnoid hemorrhage in association with a skull base ICH fed by the anterior choroidal artery.…”
Section: Discussionmentioning
confidence: 99%